Substantiation of strategic management decision directions for ensuring socio-economic security in the global economy - Svydruk, Irena; Sydorchuk, Orystlava; Myronova, Mariana; Klepanchuk, Olga; Kozlova, Valeria (Technology audit and production reserves, 2026)
The research object is Ukraine’s socio-economic security system. The research problematic is related to the necessity of selecting effective strategic decisions under conditions of increasing risks and limited institutional resources. The research is devoted to identifying directions for strategic management decisions to strengthen the state’s socio-economic security during the period of global economic and social transformations. Specifically, institutional decisions aimed at increasing investment attractiveness, regulating migration processes, and liberalizing foreign economic activity are analyzed. The methodological foundation of the research comprised regression analysis using an additive algorithm for aggregating indicators to assess the subsystems of economic security and social welfare, and a multiplicative aggregation algorithm for forming an integral indicator of socio-economic security. Identification of structural breaks of exogenous nature and empirical verification of the integral indicator’s sensitivity to macroeconomic factors were performed by introducing a binary variable following the analytical approach of time series analysis with a fixed break point. Based on the results of multi-criteria analysis, a strong moderate positive relationship was established between the level of socio-economic security and strategic decisions aimed at enhancing the state’s investment attractiveness (correlation coefficient r = 0.638), and a moderate strong positive relationship with strategic decisions aimed at liberalizing foreign economic activity (r = 0.737). The obtained results are explained by the dominant influence of institutional and economic factors on the formation of national resilience in the pre-war period and the limited role of migration processes in the short-term dynamics of macroeconomic indicators. The integration of quantitative assessment of socio-economic security with analysis of strategic management decisions enabled justification of priority directions for state policy. The theoretical significance of research is determined by the development of an approach to assessing the state’s socio-economic security that combines integral diagnostics of its condition with analysis of the impact of strategic management decisions through a system of relevant macroeconomic indicators. The practical significance is determined by the identification of strategic guidelines for state policy aimed at strengthening socio-economic security through coordinated use of instruments for investment stimulation, regulation of migration processes, and development of foreign economic cooperation.